Can someone show me the process of the product rule of this function $\displaystyle e^(xy)$ f(x)= g(x)= f'(x)= g'(x)= I need it for a implicit differentiation problem ty!
Last edited by skyslimit; Apr 28th 2009 at 12:05 PM.
Follow Math Help Forum on Facebook and Google+
Originally Posted by skyslimit Can someone show me the process of the product rule of this function $\displaystyle e^(xy)$ f(x)= g(x)= f'(x)= g'(x)= I need it for a implicit differentiation problem ty! recall, the derivative of $\displaystyle e^u$ is $\displaystyle u'e^u$, where $\displaystyle u$ is a function. here, let $\displaystyle f(x) = x$ and $\displaystyle g(x) = y$ and remember what i said in your other thread about implicit differentiation
View Tag Cloud